Protective effect of empagliflozin against palmitate-induced lipotoxicity through AMPK in H9c2 cells - Song, Min-Woo; Cui, Wenhao; Lee, Chang-Gun; Cui, Rihua; Son, Young Ho; Kim, Young Ha; Kim, Yujin; Kim, Hae Jin; Choi, Sung-E.; Kang, Yup; Kim, Tae Ho; Jeon, Ja Young; et al. (Frontiers in Pharmacology, 2023)
Sodium-glucose cotransporter 2 (SGLT2) inhibitors have recently emerged as novel cardioprotective agents. However, their direct impact on cardiomyocyte injury has yet to be studied. In this work, we investigate the underlying molecular mechanisms of empagliflozin (EMPA), an SGLT2 inhibitor, in mitigating palmitate (PA)-induced cardiomyocyte injury in H9c2 cells. We found that EMPA significantly attenuated PA-induced impairments in insulin sensitivity, ER-stress, inflammatory cytokine gene expression, and cellular apoptosis. Additionally, EMPA elevated AMP levels, activated the AMPK pathway, and increased carnitine palmitoyl transferase1 (CPT1) gene expression, which collectively enhanced fatty acid oxidation and reduced stress signals. This study reveals a novel mechanism of EMPA's protective effects against PA-induced cardiomyocyte injury, providing new therapeutic insights into EMPA as a cardioprotective agent.